SARS-CoV-2 seroprevalence among cancer patients and household caregivers in a cancer hospital: Cross-sectional survey after the second COVID-19 wave in Thailand - Teerapat Ungtrakul; Gaidganok Sornsamdang; Kamonwan Soonklang; Siriporn Saeloo; Kasiruck Wittayasak; Ornpreya Suptawiwat; Rojjanaporn Pulmanausahakul; Nanthida Phattraprayoon; Chirayu Auewarakul; Nithi Mahanonda (Elsevier, 2022)
Objectives: Patients with cancer may be at an increased risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and experience more severe outcomes. Low vaccine coverage in the early phase of the coronavirus disease 2019 (COVID-19) pandemic meant that personal and social measures to reduce viral spread were the only methods of lowering the risk of infection among cancer patients. This study explored the prevalence of SARS-CoV-2 antibodies in cancer patients and caregivers in a cancer hospital after the second COVID-19 outbreak in Thailand. Study design: Cross-sectional study. Methods: A SARS-CoV-2 seroprevalence cross-sectional survey was conducted among 200 cancer patients and 200 household caregivers in a tertiary cancer care hospital in Bangkok, Thailand. The survey took place between 4 March and May 31, 2021 - a time period covering the end of the second COVID-19 wave and the early phase of the third wave in Thailand. Results: Rigorous personal and social measures to reduce viral spread among cancer patients and caregivers lead to an extremely low prevalence of SARS-CoV2 infection (0% among cancer patients and 1% among household caregivers). Conclusion: This study demonstrates the importance of social distancing and personal hygiene measures for the prevention of SARS-CoV-2 infection, even when vaccine coverage is low.